Right Atrial Thrombus and Pulmonary Embolism in a Patient with Constrictive Pericarditis - Madhu Shukla; Jagdish Chander Mohan (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2023)
A 27-year-old male was admitted with dyspnea of sudden onset and was initially diagnosed to have acute pulmonary embolism, bilateral pleural effusion, and mild pericardial effusion. Detailed echocardiographic examination revealed echocardiographic features of constrictive pericarditis (CP), marked spontaneous contrast in inferior vena cava, and a right atrial thrombus. The patient had bilateral lung consolidation and pleural effusion presumably of tubercular origin. Intracardiac thrombi are rare in patients with CP and may impact prognosis and management strategy.